2015
DOI: 10.5897/ijnm2014.0139
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents perception of career choice of nursing among selected secondary schools in Jos, Nigeria

Abstract: The main purpose of this study was to examine the adolescents' perception and choice of nursing as a career in senior secondary schools, and to determine factors that may influence their choice and perception. The study was conducted in four selected schools in Jos metropolis. Each of these schools is unique in features. They include: two government secondary schools (urban and rural) and two private secondary schools (urban and rural). A total of 240 respondents were used for the study. A selfadministered que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The demarcation is an indication that more females feature in the nursing profession. This reflection concurs with the results of the study conducted by Ogunyewo et al ( 2015 ) in Nigeria. The study reported that 83.33% of participants who chose nursing as a career were female; furthermore, 91.25% of participants agreed that nursing is primarily for women (Ogunyewo et al 2015 ).…”
Section: Research Purposesupporting
confidence: 93%
See 2 more Smart Citations
“…The demarcation is an indication that more females feature in the nursing profession. This reflection concurs with the results of the study conducted by Ogunyewo et al ( 2015 ) in Nigeria. The study reported that 83.33% of participants who chose nursing as a career were female; furthermore, 91.25% of participants agreed that nursing is primarily for women (Ogunyewo et al 2015 ).…”
Section: Research Purposesupporting
confidence: 93%
“…This reflection concurs with the results of the study conducted by Ogunyewo et al ( 2015 ) in Nigeria. The study reported that 83.33% of participants who chose nursing as a career were female; furthermore, 91.25% of participants agreed that nursing is primarily for women (Ogunyewo et al 2015 ). Supporting the above-mentioned notion, Zamanzadeh et al ( 2013 ) stated that men because of male gender characteristics and existing public image do not often consider nursing as a career choice.…”
Section: Research Purposesupporting
confidence: 93%
See 1 more Smart Citation
“…Unlike Hong Kong (Law & Arthur ) and Nigerian students (Ogunyewo et al. ), UK students were reported to associate nursing with poor financial remuneration (Whitehead et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that parents have a substantial influence on their children's career choices. For instance, in Nigeria (Ogunyewo, Afemikhe, Ajio, & Olanlesi-aliu, 2014), (Ezeweani & Atomatofa, 2012), (Egunjobi, Salisu, & Ogunkeye, 2014), in Tanzania (Amani, 2016) in Kenya (Obwoge & Kibor, 2016). Semistructural interviews with 23 postgraduate students were conducted by (Adefulu, Farinloye, & Mogaji, 2020) on study on factors impacting postgraduate students' university choice in Nigeria, Parents have a statistical significant influence on their children's professional choices, according to research.…”
Section: Family Factor and Career Decision Makingmentioning
confidence: 99%